Respon Tanaman Hias Puring (Codiaeum variegatum L.) dan Lidah Mertua (Sansevieria trifasciata L.) Akibat Penambahan Macam Pupuk Nitrogen pada Tanah Tercemar Logam Berat Timbal (Pb) - Dwi Rizkyana Wati; Anis Sholihah; Anis Rosyidah (AGRONISMA, 2019)
The study aimed to determine the growth response of croton ornamental plants (Codiaeum variegatum L.) and tongue-in-law (Sansevieria trifasciata L.) due to the addition of nitrogen fertilizers on Pb metal contaminated soil, to know the distribution of Pb metal among types of ornamental plants due to addition of nitrogen fertilizer on the soil contaminated with Pb metal, and know the ability of croton ornamental plants (Codiaeum variegatum L.) and tongue-in-law (Sansevieria trifasciata L.) in translating Pb from root to canopy with the addition of nitrogen fertilizer. The research was conducted at the Greenhouse of the Faculty of Agriculture, Islamic University of Malang, Halal University Laboratory of the Islamic University of Malang and the Physiology Laboratory of the Faculty of Agriculture, Islamic University of Malang, which began in August to November 2018. The results showed that the types of ornamental plants and the addition of nitrogen fertilizers were tried to show a response different growths. The highest distribution of Pb in roots and canopies was T1P2 (croton plant + 100 kg N / ha ZA fertilizer) which was 0.2865 and 0.4371 ppm. The results of the calculation of Pb heavy metal TF ranged from 0.5258 to 0.8289 which means that the value of TF <1 and categorized in the phytoremediation phytostabilization strategy. The highest TF values were found in T2P2 (Sansevieria plant + 100 kg N / ha ZA fertilizer) and T1P1 (croton plant + 100 kg N / ha urea fertilizer).